Hyperlactatemia and the Outcome of Type 2 Diabetic Patients Suffering Acute Myocardial Infarction - Jovanovic Aleksandar; Peric Vladan; Snezana Markovic-Jovanovic; Radojica Stolic; Jadranka Mitic; Tanja Smilic (Journal of Diabetes Research)
Background. Increased lactate production is frequent in unregulated/complicated diabetes mellitus. Methods. Three groups, each consisting of 40 patients (type 2 diabetics with myocardial infarction, DM+AMI, nondiabetics suffering myocardial infarction, MI, and diabetics with no apparent cardiovascular pathology, DM group), were tested for pH, serum bicarbonate and electrolytes, blood lactate, and CK-MB. Results. Blood lactate levels were markedly higher in AMI+DM compared to MI group (4.54±1.44 versus 3.19±1.005 mmol/L, p<0.05); they correlated with the incidence of heart failure (ρ=0.66), cardiac rhythm disorders (ρ=0.54), oxygen saturation (ρ=0.72), CK-MB levels (ρ=0.62), and poor short-term outcome. Lactic acidosis in DM+AMI group was not always related to lethal outcome. Discussion. The lactate cutoff value associated with grave prognosis depends on the specific disease. While some authors proposed cutoff values ranging from 0.76 to 4 mmol/L, others argued that only occurrence of lactic acidosis may be truly predictive of lethal outcome. Conclusion. Both defective glucose metabolism and low tissue oxygenation may contribute to the lactate production in diabetic patients with acute myocardial infarction; high lactate levels indicate increased risk for poor outcome in this population comparing to nondiabetic patients. The rise in blood lactate concentration in diabetics with AMI was associated with increased incidence of heart failure, severe arrhythmias, cardiogenic shock, and high mortality rate.